Cartographies of infrastructural imaginations: mapping ecological utopias and dystopias in the Global South - Ernesto Valero Thomas (Global Social Challenges Journal)
This article provides the reader with a theoretical framework and a method of representing cities called cartographies of infrastructural imaginations. The study employs mapping methods from the fields of architecture, urban geography and visual cultures. The research inquires about the role of cartography in the analysis of discourses that define policies of water supply, food distribution and land-use regulation, which are three environmental challenges in cities. How can we identify and situate the urban actors that attend to such challenges in cities from the Global South? The research is empirically grounded in Mexico City, Shanghai and Bangalore, urban settlements with a history of colonial occupation in previous centuries. Their foreign interventions still shape urban imaginaries of these cities. The method of blending photographic analysis with maps aims to offer objective precision of geographical data and subjective street-level views of local stories. The intention is to understand where the infrastructural ideas come from, and how imaginaries flow to communicate visions about the development of the city. A central task here is to frame how power structures interact and represent their interests via utopian and dystopian narratives.